2018
DOI: 10.1126/scisignal.aar8371
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic RAS isoforms show a hierarchical requirement for the guanine nucleotide exchange factor SOS2 to mediate cell transformation

Abstract: About a third of tumors have activating mutations in ,, or , genes encoding guanosine triphosphatases (GTPases) of the RAS family. In these tumors, wild-type RAS cooperates with mutant RAS to promote downstream effector activation and cell proliferation and transformation, suggesting that upstream activators of wild-type RAS are important modulators of mutant RAS-driven oncogenesis. The guanine nucleotide exchange factor (GEF) SOS1 mediates KRAS-driven proliferation, but little is understood about the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(96 citation statements)
references
References 66 publications
(97 reference statements)
16
80
0
Order By: Relevance
“…The relevance of 3D culture systems extends to the identification of novel therapeutic targets and therapeutic combinations. We recently showed that SOS2 is specifically required for PI3K-dependent protection from anoikis in KRAS-mutated NSCLC cells (32) and SOS2 deletion synergizes with MEK inhibition to kill KRAS mutated cells only under 3D culture conditions (31). Here, we show marked synergy between vertical inhibition of EGFR and SOS1 in EGFR mutated cancer cells, but only under 3D culture conditions (Fig.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The relevance of 3D culture systems extends to the identification of novel therapeutic targets and therapeutic combinations. We recently showed that SOS2 is specifically required for PI3K-dependent protection from anoikis in KRAS-mutated NSCLC cells (32) and SOS2 deletion synergizes with MEK inhibition to kill KRAS mutated cells only under 3D culture conditions (31). Here, we show marked synergy between vertical inhibition of EGFR and SOS1 in EGFR mutated cancer cells, but only under 3D culture conditions (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…However, simultaneous inhibition of multiple RTKs with osimertinib may be required to eliminate oncogenic shift to alternative RTKs (8). Downstream 5 pharmacologic synergy, we demonstrate that SOS1 inhibition using BAY-293 synergizes with osimertinib only under 3D spheroid culture conditions, and in doing so add to the growing evidence that pharmacologic assessment of novel therapeutics designed to treat cancer must be performed under 3D culture conditions (27,31,(34)(35)(36). By assessing the pharmacologic landscape of EGFR/RAS pathway inhibitors, we demonstrate that inhibition of proximal signaling is required to synergize with osimertinib, and that combined EGFR and SOS1 inhibition synergizes to inhibit RAS effector signaling in 3D culture.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Decreased affinity for the RAS-GAP NF1 (II) by the G13D mutant protein enables GAP-and EGFR-dependent regulation of wild-type RAS, thereby retaining sensitivity to EGFR inhibitors in KRAS G13D mutant cells. Sheffels et al (29) identified a role for the RAS-GEF SOS2 (III) in promoting WT HRAS activation of AKT to support MT KRAS-induced transformation of mouse fibroblasts in 3D growth culture conditions. degradation of RAS or release of nucleotide but instead locally altered RAS SWI structure that impaired both SOS1 and RAF effector binding.…”
Section: Direct Ras Targetingmentioning
confidence: 99%